2018
DOI: 10.1111/raq.12323
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers of DNA quality in cryopreserved fish sperm: impact on gene expression and embryonic development

Abstract: Sperm DNA quality and gene expression are crucial for early embryo development. Abnormal genomic processes can cause irreversible damage to totipotent cells, thereby altering the capacity for cell differentiation. Cryopreservation is a complex procedure that exposes cells to extreme conditions; it is therefore important to determine whether cryopreservation affects genomic stability. Despite this, few studies have focused on the effects of cryopreservation on the genomic stability of fish sperm. Thus, informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 82 publications
0
29
0
Order By: Relevance
“…The high percentage of incompletely hatched embryos in CENSALBA families at the highest and lowest temperatures could be an indicator of thermal stress, and it is striking that F1 families, in agreement with Ineno et al (2005), showed higher percentages of incompletely hatched embryos only at the lowest temperature (Figure 6). The general absence of significant differences between CENSALBA and F1 families observed here could be expected as a consequence of late zygotic genome activation (Figueroa et al, 2018;Lindeman & Pelegri, 2010).…”
Section: Discussionmentioning
confidence: 47%
“…The high percentage of incompletely hatched embryos in CENSALBA families at the highest and lowest temperatures could be an indicator of thermal stress, and it is striking that F1 families, in agreement with Ineno et al (2005), showed higher percentages of incompletely hatched embryos only at the lowest temperature (Figure 6). The general absence of significant differences between CENSALBA and F1 families observed here could be expected as a consequence of late zygotic genome activation (Figueroa et al, 2018;Lindeman & Pelegri, 2010).…”
Section: Discussionmentioning
confidence: 47%
“…Alternation of chromosome material, Y chromosome deletion, and ploidy level are among factors that affect fertility. The integrity of sperm DNA correlates with fertilization and embryonic development in fishes [93,94]. Fertility threat has been frequently reported in polyploid fish, which were associated with failure of testicular development [95], enlarged head size making penetration of sperm through a normal-sized micropyle difficult [96,97], reduced sperm production [84,98], and increased abnormal sperm with malformation of the head, mitochondria, and flagellum resulting in decreasing motility and velocity [84,99].…”
Section: Sperm Genomementioning
confidence: 99%
“…More than a dozen studies in fish have assessed the DNA integrity of post-thaw spermatozoa (Labbé et al 2001;Zilli et al 2003;Cabrita et al 2005b and its impact on gene expression and embryo development, are described and discussed by Figueroa et al (2020). According to the majority of these studies, cryopreservation can damage sperm DNA.…”
Section: Dna Damagementioning
confidence: 99%
“…Specific details of DNA damage, and its impact on gene expression and embryo development, are described and discussed by Figueroa et al . (2020). According to the majority of these studies, cryopreservation can damage sperm DNA.…”
Section: Dna Damagementioning
confidence: 99%